2020
DOI: 10.3390/agronomy10101481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt Stress on Fruit Antioxidant Capacity of Wild (Solanum chilense) and Domesticated (Solanum lycopersicum var. cerasiforme) Tomatoes

Abstract: The effects of salt on the quality of fruits were investigated in order to compare the impact of salt on key fruit properties of the cultivated domesticated tomato species (Solanum lycopersicum) and its wild halophyte relative Solanum chilense. To this end, cherry tomato plants (S. lycopersicum var. cerasiforme) and from accession LA4107 (S. chilense) were maintained for 112 days in the absence or presence of NaCl (40 and 80 mM) in nutrient solution. Among others, salinity decreased fruit weight and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 56 publications
1
14
0
1
Order By: Relevance
“…However, lycopene was cited in the literature for its antioxidant properties [21] [22] [23]. The results of the present study are close to those of [5] working on the effect of salt stress on the antioxidant quality of tomato fruits. The latter did show a significant correlation between the phenol content of tomato fruits and their DPPH and FRAP antiradical activities, but no correlation between these antiradical activities and the lycopene content of the fruits.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, lycopene was cited in the literature for its antioxidant properties [21] [22] [23]. The results of the present study are close to those of [5] working on the effect of salt stress on the antioxidant quality of tomato fruits. The latter did show a significant correlation between the phenol content of tomato fruits and their DPPH and FRAP antiradical activities, but no correlation between these antiradical activities and the lycopene content of the fruits.…”
Section: Discussionsupporting
confidence: 86%
“…The latter did show a significant correlation between the phenol content of tomato fruits and their DPPH and FRAP antiradical activities, but no correlation between these antiradical activities and the lycopene content of the fruits. Nevertheless, as tomato is the primary source of lycopene for humans [8] [21] [5], results of this study showed that A. indica at 10% (Ai1) had a good effect on its accumulation in fruits. This extract also promotes the accumulation of sugars in the fruit.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, abiotic stress tolerance mechanisms remain largely unknown in this species compared to other wild tomato relatives [ 25 , 26 ]. Some studies investigated the physiological mechanisms underlying drought and salt tolerance in S. chilense , but they focused on one or a limited number of populations [ 23 , 25 , 27 , 28 , 29 , 30 , 31 , 32 ]. No study to date has investigated the resistance of this species to heat and the combination of drought and heat.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian mengenai respon tanaman terhadap salinitas telah banyak dilakukan pada tanaman hortikultura dari famili Solanaceae, seperti pada kentang (Ahmed et al, 2020), terung (Sobir, et al, 2018), tomat (Martínez et al, 2020), paprika (Giorio et al, 2020), dan cabai (Mustafa et al, 2019). Akan tetapi, penelitian mengenai salinitas pada cabai berfokus pada spesies Capsicum annum L. sedangkan respon C. frutescens terhadap salinitas masih banyak berfokus pada morfologi.…”
Section: Pendahuluanunclassified